2022
DOI: 10.1002/jbm.b.35067
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo assessment of a 3D printable gelatin methacrylate hydrogel for bone regeneration applications

Abstract: Bone tissue engineering (BTE) has made significant progress in developing and assessing different types of bio-substitutes. However, scaffolds production through standardized methods, as required for good manufacturing process (GMP), and posttransplant in vivo monitoring still limit their translation into the clinic. 3D printed 5% GelMA scaffolds have been prepared through an optimized and reproducible process in this work. Mesenchymal stem cells (MSC) were encapsulated in the 3D printable GelMA ink, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…It is encouraging that the η * (figure 2(C)) and G ′ (figure 2(D)) of the bioinks were inferior (below 100 Pa s and 0.5 kPa, respectively) at cartridge temperature (about 20 • C) and very high (above 750 Pa s and 5 kPa, respectively) at platform temperature (10 • C), which were favorable for bioinks extrusion printing from the needle and scaffold accelerating molding on the platform. The phenomenon was similar to the thermosensitive bioinks in recent studies [16,18,63]. In addition, due to the increase of nHAp content, the relative concentration of Gel decreased, which resulted in the pre-gel temperature of dGQH bioinks decreasing compared to dGQ bioink (figure 2(E)).…”
Section: Synthesis and Rheological Properties Of The Bioinkssupporting
confidence: 84%
“…It is encouraging that the η * (figure 2(C)) and G ′ (figure 2(D)) of the bioinks were inferior (below 100 Pa s and 0.5 kPa, respectively) at cartridge temperature (about 20 • C) and very high (above 750 Pa s and 5 kPa, respectively) at platform temperature (10 • C), which were favorable for bioinks extrusion printing from the needle and scaffold accelerating molding on the platform. The phenomenon was similar to the thermosensitive bioinks in recent studies [16,18,63]. In addition, due to the increase of nHAp content, the relative concentration of Gel decreased, which resulted in the pre-gel temperature of dGQH bioinks decreasing compared to dGQ bioink (figure 2(E)).…”
Section: Synthesis and Rheological Properties Of The Bioinkssupporting
confidence: 84%
“…Moreover, the performance of 3D printed gelatin methacrylate hydrogel has formerly been investigated after implantation in rat condyle defects. Whereas optimal tissue integration was observed via histology, no signs of fibrotic encapsulation or inhibited bone formation were attained [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that gelMA and MSCs together have enhanced ability for the differentiation of the MSCs due to the porous nature of the gelMA. The MSCs that were encapsulated with the gelMA showed potential for future BTE experiments [77]. Beyond scaffolds, 3D printing can be used for a wide array of bone repair applications, including screws, plates, and gels [32].…”
Section: Hydrogels In 3d Bioprinting and Where To Improvementioning
confidence: 99%